Optimalisasi Strategi Pemasaran Digital FREEIDEA Entertainment dalam Pengelolaan Branding BENDLANCAR: Perspektif Komunikasi dan Dakwah - Yasin, Nur; Rahman, Fairizal; Rizky Fauzi, Reza; Fathurahman, Irfan; Fuad Husain, Rendy; Rizky Kurniawan, Muhammad; Dinar Yoga Pratama, Mochamad (KOMUNIDA : Media Komunikasi dan Dakwah, 2023)
This study describes the strategy of FREEIDEA Entertainment in the branding management of clients and to be able to share their knowledge and experiences in the field of digital communication and marketing. In addition, this research was conducted with the aim of knowing and understanding the digital marketing strategies implemented by FREEIDEA Entertainment in managing brands. This research will also be a reference for sharing knowledge in concept development of digital marketing as well as research related to marketing in the digital field. This study uses qualitative research with a case study approach and constructivism paradigm. This study explores digital marketing and discusses it using a brand perspective, so this research will present a different angle of explanation, namely a digital marketing consultant. FREEIDEA Entertainment is one of the companies engaged in the digital marketing consultant in Kediri City. FREEIDEA Entertainment always applies accurate and precise strategies when doing digital marketing for its clients. This study finds that FREEIDEA Entertainment uses digital media channels, the SOSTAC strategy, and improves performance and evaluation in managing brands.